Electronic Device for Satellite Backup of Automatic Vehicle Location Equipment Using the Iridium Network - Guerrero Rodríguez, Néstor; Paz Penagos, Hernán (Bogotá, 2020)
Context: This paper presents the design and development of an electronic device that operates as a satellite backup channel for automatic vehicle location (AVL) equipment, whose only communication channel is the cellular network. Method: The design, manufacture and assembly of the hardware followed 4 phases, and it was aligned with the IPC 2221 standard. This allowed improving the design experience and guaranteed the correct electrical operation in the final product. Results: The information sent by the developed device corresponds to the data generated by the AVL device, which indicates that the information processing was correctly designed. Additionally, it was possible to obtain a functional and versatile device in which the blocks were correctly integrated; its firmware was designed to receive future updates that improved and expanded its capacity and compatibility with other devices. Conclusions: The final product, which works with the Iridium network, seeks to satisfy the technological requirements of the freight transport sector in Colombia with a low-cost, versatile, and easily integrated solution. The implementation of this type of technologies expands the capacity of tracking mobile assets, even in places where there is no cellular network coverage.

Contexto: Este articulo presenta el diseño y desarrollo de un dispositivo electrónico, que funciona como canal de respaldo satelital para equipos de localización vehicular automática (AVL), cuyo único canal de comunicación es la red celular. Método: El diseño, fabricación y ensamblaje del hardware siguió cuatro fases y estuvo alineado con el estándar IPC 2221. Esto permitió mejorar la experiencia del diseño y garantizó el correcto funcionamiento eléctrico en el producto final. Resultados: La información enviada por el dispositivo desarrollado corresponde a los datos generados por el dispositivo AVL, lo que indica que el procesamiento de la información fue diseñado correctamente. Además, fue posible obtener un dispositivo funcional y versátil cuyos bloques se integraron correctamente; su firmware fue diseñado para recibir futuras actualizaciones que mejoraran y ampliaran su capacidad y compatibilidad con otros dispositivos. Conclusiones: El producto final, que opera con la red Iridium, busca satisfacer las necesidades tecnológicas del sector de transporte de carga en Colombia con una solución versátil, de bajo costo y de fácil integración. Con el uso de este tipo de tecnologías, se amplía la capacidad de rastrear activos móviles, aun en zonas donde no existe cobertura de redes celulares.
Dispositivo electrónico para respaldo satelital de equipos de localización vehicular automática, utilizando la red Iridium
Keywords: Sistema de posicionamiento global; Global Positioning System; Servicios basados en localización; Location-based services; Transporte terrestre; Land transport; AVL equipment; Satellite backrest; Iridium network; Equipos AVL; Canal de respaldo satelital; Red Iridium